1996
DOI: 10.1046/j.1365-2141.1996.d01-1871.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale DNA typing for human platelet alloantigens by PCR‐PHFA (preferential homoduplex formation assay)

Abstract: Alloimmunization against human platelet alloantigens (HPA) is known to be involved in disorders such as neonatal alloimmune thrombocytopenic purpura, posttransfusion purpura, and refractoriness to platelet transfusion therapy. HPA typing is essential in diagnosis and management of patients. Therefore a reliable and speedy method is necessary for HPA typing. We have successfully applied a new DNA typing method, PCR-preferential homoduplex formation assay (PHFA) method, to typing for the HPA-1, -2, -3, -4, -5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Genotyping of CD80 downstream promoter region using PCR-PHFA PCR-PHFA has been successfully applied to the allele typing for HLA-DPB1, 45 human platelet antigens (HPAs), 48 and Fc␥RIIIB, 24 and we have recently established the allele typing method of human TNFA 5′-flanking region using PCR-PHFA. 49 The downstream promoter regions of the genomic DNA from three samples possessing (−79C/C, −7T/T, +5C/C), (−79G/G, −7T/T, +5C/C) and (−79C/C, −7C/C, +5A/A) genotypes, respectively, were amplified using biotin-labeled forward primer and DNP-labeled reverse primer and were used as the standard DNAs.…”
Section: Pcr Amplification Of Cd80 and Cd86mentioning
confidence: 99%
“…Genotyping of CD80 downstream promoter region using PCR-PHFA PCR-PHFA has been successfully applied to the allele typing for HLA-DPB1, 45 human platelet antigens (HPAs), 48 and Fc␥RIIIB, 24 and we have recently established the allele typing method of human TNFA 5′-flanking region using PCR-PHFA. 49 The downstream promoter regions of the genomic DNA from three samples possessing (−79C/C, −7T/T, +5C/C), (−79G/G, −7T/T, +5C/C) and (−79C/C, −7C/C, +5A/A) genotypes, respectively, were amplified using biotin-labeled forward primer and DNP-labeled reverse primer and were used as the standard DNAs.…”
Section: Pcr Amplification Of Cd80 and Cd86mentioning
confidence: 99%
“…HPA‐4b–incompatible NAIT represents the majority (72%) of HPA‐related NAIT cases in Japan, 24 and cases due to HPA‐2b, HPA‐3a, HPA‐5b, and HPA‐6b have also been reported 22 . Furthermore, before the present study, the low‐frequency HPA‐7 to HPA‐13 antigens were found to be monomorphic in Asian (including Japanese) populations 2,4,25 …”
mentioning
confidence: 43%
“…The double–labeled standard DNA was captured on a streptavidin–coated microtiter plate and detected using an alkaline–phosphatase–conjugated anti–DNP antibody with a chromogenic substrate, as described previously [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we developed a new DNA typing method, the PCR–preferential homoduplex formation assay (PHFA) [17], and applied it to the typing of human platelet alloantigens (HPA)–1, –2, –3, –4, –5, and –6 systems [18]. Now, we have applied this method to DNA typing of neutrophil–specific antigens, namely, NA1, NA2, and SH, located on the neutrophil FcγRIIIb, and determined the FcγRIIIB gene frequencies in the Japanese population.…”
Section: Introductionmentioning
confidence: 99%